The oncogenic roles of GPR176 in ovarian cancer: a molecular target for aggressiveness and gene therapy - Ning Yang; Wen-jing Yun; Zheng-guo Cui; Hua-chuan Zheng (Journal of Obstetrics and Gynaecology)
Background At present, the discovery of new biomarkers is of great significance for the early diagnosis, treatment and prognosis assessment of ovarian cancer. Previous findings indicated that aberrant G-protein-coupled receptor 176 (GPR176) expression might contribute to tumorigenesis and subsequent progression. However, the expression of GPR176 and the molecular mechanisms in ovarian cancer had not been investigated.Methods GPR176 expression was compared with clinicopathological features of ovarian cancer using immunohistochemical and bioinformatics analyses. GPR176-related genes and pathways were analysed using bioinformatics analysis. Additionally, the effects of GPR176 on ovarian cancer cell phenotypes were investigated.Results GPR176 expression positively correlated with elder age, clinicopathological staging, tumour residual status, and unfavourable survival of ovarian cancer, but negatively with purity loss, infiltration of B cells, and CD8+ T cells. Gene Set Enrichment Analysis showed that differential expression of GPR176 was involved in focal adhesion, ECM-receptor interaction, cell adhesion molecules and so on. STRING and Cytoscape were used to determine the top 10 nodes. Kyoto Encyclopaedia of Genes and Genomes analysis indicated that GPR176-related genes were involved in the ECM structural constituent and organisation and so on. GPR176 overexpression promoted the proliferation, anti-apoptosis, anti-pyroptosis, migration and invasion of ovarian cancer cells with overexpression of N-cadherin, Zeb1, Snail, Twist1, and under-expression of gasdermin D, caspase 1, and E-cadherin.Conclusion GPR176 might be involved in the progression of ovarian cancer. It might be used as a biomarker to indicate the aggressive behaviour and poor prognosis of ovarian cancer and a target of genetic therapy.